Model Pengembangan Kompetensi Tafsir Al-Qur’an (Malakah Tafsiriyah) - Muhammad (Jurnal Pendidikan Agama Islam, 2026)
This study aims to construct a theoretical-practical model for developing holistic and integrative Qur’anic exegesis competency (malakah tafsiriyah), in response to the phenomenon of weak methodological foundations in contemporary interpretation. This study uses a qualitative approach with in-depth content analysis of Arabic-language scientific sermon manuscripts discussing the concept of malakah tafsiriyah and recent secondary literature. The results identify and analyze ten fundamental pillars for forming malakah tafsiriyah: (1) Ta’zhim al-Qur’an (2) al-Farah bi al-Qur’an, (3) Idamatu al-Qirā’ah wa al-Nazhar, (4) Salāmatu al-Qalb, (5) Talaqqi al-Tafsīr bi Sullūki al-Jādah al-Mūsilah, (6) Ma’rifatu Ushūl al-Tafsīr wa Qawā’idihi, (7) Dirāsatu ‘Ulūm al-Qur’an, (8) Ishābatu Hazzin Wāfirin min ‘Ulūm al-Ālah , (9) Istīfā’u Qadarin Matīnin min ‘Ulūm al-Dīn, and (10) al-I’tinā’ bi Tafsīr al-Qur’ān bi al-Qur’ān. This model asserts that exegesis competency is not merely cognitive mastery but a malakah (ingrained disposition) integrated within the self, encompassing spiritual, affective, and psycho-intellectual dimensions. The findings conclude that implementing this ten-pillar-based model in the curriculum of Islamic higher education in Indonesia can address the challenge of developing competent, characterful, and contextual interpreters. This study contributes a systematic and character-oriented framework for developing an exegesis curriculum.